Assessment of the Solar-Coupled Earth Air Heat Exchanger (EAHE) System for Sustainable Residential Cooling - kumar Khare, Girish; Kumar Nikam, Sachin (Journal of Neonatal Surgery, 2025)
As the need for sustainable and energy-efficient cooling solutions in residential buildings increases, Earth Air Heat Exchanger (EAHE) systems have surfaced as a viable alternative to traditional HVAC systems. This research examines the design, modeling, and experimental assessment of three configurations of Earth Air Heat Exchangers (EAHE)—Parallel (Existing), Series, and Modified—for residential cooling applications. The efficacy of each arrangement was evaluated under actual summer circumstances in Gwalior, India. The Modified EAHE system was combined with a Solar Chimney to improve passive airflow and thermal efficiency. ANSYS FLUENT was used to perform Computational Fluid Dynamics (CFD) simulations for modeling heat transfer and airflow dynamics across various EAHE setups. The simulation results were corroborated by experimental testing, demonstrating a robust link between expected and observed performance. The Modified EAHE system achieved a maximum temperature drop of 14°C, with air changes per hour (ACH) values between 4.19 and 5.56, in accordance with international indoor air quality requirements. The incorporation of the solar chimney enhanced natural ventilation and decreased energy reliance. This study highlights the viability of solar-assisted EAHE systems as economical and environmentally sustainable cooling solutions for structures in arid and high-temperature regions. The results underscore the impact of critical design parameters—such as pipe length, burial depth, airflow velocity, and soil characteristics on the overall efficiency of the system. The verified CFD models provide a dependable foundation for further design optimization and performance prediction. This research advances the focus on passive and renewable energy thermal comfort solutions, facilitating scalable and sustainable implementation in the built environment.